Research in the Digital Transformation or the Library System - Nagy, Andor (Bobcatsss, 2023)
Libraries have always tried to adapt to changing social needs, the development of the sciences, and the emergence of new technological solutions. Consider, for example, the invention of book printing or the mass distribution of printed products and the resulting current bibliographies or even to the gradually emerging reference service. Undoubtedly, the next major stage in the development of library science will be induced by the spread of computer science and informatics. More and more areas of life are digitizing and people are increasingly relying on electronic sources to obtain information thus, the use of digital remotely accessible services has become commonplace. All of this involves a transformation in people’s expectations of the library, and libraries are trying to keep up with emerging needs. More and more libraries offer thematic collections that are available electronically so eventually the digital, remote access use of services become daily. They also enable electronic document lending, online events, e-learning courses and other services that have recently been integrated into the library’s service offering. In my research, I would like to explore how the Hungarian, European and US librarian profession has reacted to the fundamental transformation of the societal demands placed on libraries in the last two decades whether their electronic services have been able to respond appropriately to new societal needs and are still able to meet the role set out in the 1994 IFLA and UNESCO Manifesto on Public Libraries. The aim of my research is to review the transformation of the library service offer over the last two decades, to compare the development direction of Hungarian libraries with international (European and US) trends, and to use new statistics, research results and needs assessments bypass as well as the extent to which libraries have been able to adapt to significantly changed user needs and whether their newly developed services are in line with them.